Inter-annual Variability of the Carbonate System in the Hypoxic Upper Pearl River Estuary in Winter - Guo, Xianghui; Song, Xue; Gao, Ying; Luo, Yaohua; Xu, Yi; Huang, Tao; Wang, Lifang (Frontiers in Marine Science, 2020)
Hypoxia has become a universal environmental and ecological problem in recent decades. The Pearl River estuary (PRE), the largest estuary in Southern China, is hypoxic year-round in the upper estuary. This study reports the inter-annual variation between 2005 and 2019 in the carbonate system of the hypoxic upper PRE in winter. In January 2005, both DIC and TA concentrations were >3000 umol kg-1 at the upstream-most station and decreased sharply downstream. However, DIC and TA were lower, with concentrations of 2300 and 1950 umol kg-1, respectively, at the upstream-most in January 2019. At salinities >15, both DIC and TA were conservative and reached steady values at the downstream seawater end-member. The upstream-most station was taken as an example to quantify the influences of biogeochemical processes on DIC and TA, including CO2 degassing, organic carbon oxidation, pelagic nitrification, CaCO3 dissolution and benthic release. Among the biogeochemical process, a decrease in CaCO3 dissolution (from 734.4 umol kg-1 in 2005 to 168.9 umol kg-1 in 2019) was the major factor driving the decreases of DIC and TA in 2019. In the context of global change, inter-annual variability in biogeochemical process should receive more attention.